PENGARUH METODE BERCERITA MENGGUNAKAN MEDIA POP-UP BOOK TERHADAP KEMAMPUAN MENYIMAK ANAK KELOMPOK B DI TAMAN KANAK-KANAK MENTARI KABUPATEN TAKALAR - Ainul Annisa; Muhammad Akil Musi; Azizah Amal (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study was to determine the differences in children's listening skills before and after being treated with the storytelling method using pop-up book media and to determine whether or not there was an effect of storytelling method using pop-up book media on children's listening ability in Mentari Kindergarten, Kabupaten Mentari. Takalar. The approach in this research is quantitative with the type of research is Quasi Experimental Design. The population in this study were groups A and B in Mentari Kindergarten, Takalar Regency totaling 26 children and the sampling used was purposive sampling with 14 children, 7 children as the experimental group and 7 children as the control group. Data collection techniques used are tests, observations and documentation. The data analysis technique used is descriptive statistical analysis and nonparametric analysis. The results showed that there were differences in children's listening skills before and after being treated with the storytelling method using pop-up book media and there was an effect of storytelling using pop-up book media on children's listening skills in Mentari Kindergarten, Takalar Regency.